Writing apprehension and writing skills on English department students: A correlational design - Geminastiti Sakkir; Nurul Fadhilah Suardi; Syarifuddin Dollah; Jamaluddin Ahmad (Center for Humanities and Innovation Studies, 2022)
Using two different types of instruments—a questionnaire to determine students' writing apprehension and a writing test using descriptive texts to decide students' writing skills—this study investigated the correlation between writing apprehension and students' writing skills. This study used quantitative correlational research, and the English department served as the study's target population. Additionally, the researchers employed cluster sampling and correlational design, which can choose a representative sample and represent the population. To conduct the analysis, the researchers chose one class as a sample, and thirty-five students from the third semester were chosen as the sample. According to the researchers, writing apprehension and students' writing skills were shown to be negatively correlated, who concluded that the correlation between the two was r = -0.642. The inverse correlation indicates that students did not perform as good as on writing tests the more frequently they worry about writing. Additionally, it can be inferred that there is a strong correlation between students' writing skills and their level of writing apprehension. Future researchers can focus on strategies for reducing fear of writing or what methods and teaching are proper to reduce students' high levels of fear.